An Analysis of Mexican Culture “Dia De Los Muertos” in Coco Animation Film - Lestari, Rina; Tiana, Delis Meta (Universitas Muhammadiyah Gorontalo, 2024)
This research explores the Mexican culture and how animation films can convey foreign traditions, such as